Analysis of field synergy principle and the relationship between secondary flow and heat transfer in double-layered microchannels with cavities and ribs. (October 2016) - Zhai, Yuling; Li, Zhouhang; Wang, Hua; Xu, Jianxin
Highlights: Two new types of double-layered microchannels with different arrangement of cavities and ribs are presented. The intensity of secondary flow and field synergy principle are evaluated. The relationship between the secondary flow and heat transfer is investigated. Abstract: The characteristic of flow and heat transfer in double-layered microchannels with cavities and ribs is investigated numerically. The intensity of secondary flow ( Se ) and field synergy principle are used to evaluate the heat transfer performance. The results show that the effect of arrangement of cavities and ribs on friction factor and Nusselt number is obviously. The opposite cavities and aligned ribs aside the microchannel wall (Channel C) exhibit the highest intensity of secondary flow, thus resulting in the highest Nusselt number and pressure drop simultaneously. From the view point of field synergy principle, Channel C has the smallest value of field synergy angle β and the highest value of field synergy number Fc, which indicates the best synergy relationship between velocity and temperature fields. Lastly, a thermal enhanced factor is used to evaluate the comprehensive effect of flow friction and heat transfer. The thermal enhanced factor of Channel C increases with Se firstly and then decreases. The offset cavities and ribs aside the microchannel wall (Channel B) shows the best comprehensive effect in the range of Reynolds number and Se studied here. Therefore, Reasonable geometric design of double-layered microchannels must be considered to enhance heat transfer and decrease pressure drop as well.